Dynamic change of direction, isometric strength, and psychological readiness in final phase ACLR athletes: an integrated approach - JPJ Stofberg; Mariaan van Aswegen; Mark Kramer (BMC Musculoskeletal Disorders)
Abstract Background Rehabilitation following successful ACL reconstruction (ACLR) requires restoring physical strength, neuromuscular function, and psychological readiness. However, the interplay between reactive agility, strength, and psychological confidence across rehabilitation phases remains unclear, particularly when compared to uninjured individuals. This study investigates the interrelationships between the reactive agility test (RAT), the isometric mid-thigh pull (IMTP), and the anterior cruciate ligament return-to-sport after injury (ACL-RSI) scale across three rehabilitation phases (Phase 4 [P4], return-to-play [RTP]1, and RTP2) following ACLR. The aim was to examine how reactive agility, strength, and psychological readiness evolve over time and compare ACLR participants to a healthy control group. Methods Fifteen ACLR participants (15–27 years old) and thirty healthy controls (18– 30 years old) completed RAT, isometric mid-thigh pull (IMTP), and ACL-RSI assessments. ACLR participants were assessed at three rehabilitation phases (P4, RTP1, and RTP2), while controls completed a single testing session. Repeated measures analyses were used to track mean changes in performance across rehabilitation phases, and between-group comparisons were conducted using independent samples tests. Results ACL-RSI scores improved significantly across phases (p = 0.001), exceeding the smallest worthwhile change (SWC), indicating progressive psychological recovery. Reactive agility improved, with faster left-side decision-making (split 2) from P4 to RTP1 (p = 0.037), while right-side agility remained stable but met the SWC threshold (1.1%). Limited between-group differences in total RAT times and sub-phases suggest ACLR participants regained agility comparable to controls. IMTP strength plateaued after RTP1, reinforcing the greater role of agility and cognitive factors within the RTP framework. Conclusions Reactive agility and psychological confidence progressively improved post-ACLR, with decision-making speed recovering earlier than acceleration ability. Minimal between-group differences suggest rehabilitation effectively restores agility, but directional asymmetries and plateaued strength warrant targeted interventions. Future research should explore neurocognitive training to optimize RTP outcomes and minimize re-injury risk. Trial registration Clinical trial number not applicable.